Can youth employment programmes work? A programme theory evaluation of the work and skills placement programme - Smith, Gail (Organisational Psychology, 2026)
In South Africa, more than one in three youth are unemployed and available to work. Youth employment programmes (YEPs) offer job-skills training and employment services and aim to promote youth's employment prospects. Despite their prevalence worldwide few YEPs have been successful in reducing youth unemployment. In the few cases of success, little is known about how and why YEPs work to mediate youth's entry to employment. This dissertation presents the findings of a programme theory evaluation of the Work and Skills Placement (WSP) programme, a YEP co-implemented by the Western Cape's Department of Economic Development and its company partners. Programme theory evaluation first seeks to unpack how and why programmes can (should) work before assessing whether programmes do work. Through this formative evaluation the theories or ‘change stories' of the Department and six host companies were described and then assessed for plausibility by comparing stakeholders' views to evidence in the YEP literature. The results indicated that while the programme included several best practice features, the current WSP programme may work to improve youth's employability but is not plausible in improving youth employment. Key recommendations to enhance the programme's plausibility include adding complementary interventions to stimulate companies' growth and enhancing youth's employability by intensifying the jobskills training pathways. This evaluation contributes to improving the WSP programme's design and success pathways, as well as the current limited knowledge base of how YEPs can or should work to successfully improve youth's employment prospects.